Conditional survival and long‐term efficacy with nivolumab plus ipilimumab versus sunitinib in patients with advanced renal cell carcinoma - Motzer, Robert J.; McDermott, David F.; Escudier, Bernard; Burotto, Mauricio; Choueiri, Toni K.; Hammers, Hans J.; Barthélémy, Philippe; Plimack, Elizabeth R.; Porta, Camillo; George, Saby; Powles, Thomas; Donskov, Frede; et al. (Cancer, 2022)
Background Conditional survival estimates provide critical prognostic information for patients with advanced renal cell carcinoma (aRCC). Efficacy, safety, and conditional survival outcomes were assessed in CheckMate 214 (ClinicalTrials.gov identifier NCT02231749) with a minimum follow‐up of 5 years. Methods Patients with untreated aRCC were randomized to receive nivolumab (NIVO) (3 mg/kg) plus ipilimumab (IPI) (1 mg/kg) every 3 weeks for 4 cycles, then either NIVO monotherapy or sunitinib (SUN) (50 mg) daily (four 6‐week cycles). Efficacy was assessed in intent‐to‐treat, International Metastatic Renal Cell Carcinoma Database Consortium intermediate‐risk/poor‐risk, and favorable‐risk populations. Conditional survival outcomes (the probability of remaining alive, progression free, or in response 2 years beyond a specified landmark) were analyzed. Results The median follow‐up was 67.7 months; overall survival (median, 55.7 vs 38.4 months; hazard ratio, 0.72), progression‐free survival (median, 12.3 vs 12.3 months; hazard ratio, 0.86), and objective response (39.3% vs 32.4%) benefits were maintained with NIVO+IPI versus SUN, respectively, in intent‐to‐treat patients (N = 550 vs 546). Point estimates for 2‐year conditional overall survival beyond the 3‐year landmark were higher with NIVO+IPI versus SUN (intent‐to‐treat patients, 81% vs 72%; intermediate‐risk/poor‐risk patients, 79% vs 72%; favorable‐risk patients, 85% vs 72%). Conditional progression‐free survival and response point estimates were also higher beyond 3 years with NIVO+IPI. Point estimates for conditional overall survival were higher or remained steady at each subsequent year of survival with NIVO+IPI in patients stratified by tumor programmed death ligand 1 expression, grade ≥3 immune‐mediated adverse event experience, body mass index, and age. Conclusions Durable clinical benefits were observed with NIVO+IPI versus SUN at 5 years, the longest phase 3 follow‐up for a first‐line checkpoint inhibitor‐based combination in patients with aRCC. Conditional estimates indicate that most patients who remained alive or in response with NIVO+IPI at 3 years remained so at 5 years. In the longest phase 3 follow‐up of a checkpoint inhibitor combination therapy in advanced renal cell carcinoma together with the first long‐term conditional survival analyses in the CheckMate 214 trial, nivolumab plus ipilimumab demonstrated durable survival and response benefits versus sunitinib at 5 years. These results establish a new benchmark for both the magnitude and durability of benefit possible with first‐line immunotherapy‐based regimens in this setting.